Consecutive and Selective Double Methylene Insertion of Lithium Carbenoids to Isothiocyanates: A Direct Assembly of Four‐Membered Sulfur‐Containing Cycles. (13th October 2021) - Senatore, Raffaele; Malik, Monika; Langer, Thierry; Holzer, Wolfgang; Pace, Vittorio
Abstract: A formal CH2 −CH2 homologation conducted with C1 carbenoids on a carbon electrophile for the obtainment of a four‐membered cycle is reported. The logic proposes the consecutive delivery of two single nucleophilic CH2 units to an isothiocyanate—as competent electrophilic partner—resulting in the assembling of a rare imino‐thietane cluster. The single synthetic operation procedure documents genuine chemocontrol, as indicated by the tolerance to various reactive elements decorating the starting materials. Significantly, the double homologation protocol is accomplished directly on a carbon electrophile, thus not requiring the installation of heteroatom‐centered manifolds (e.g. boron). Abstract : A formal CH2 −CH2 homologation conducted with C1 carbenoids on a carbon electrophile for the obtainment of a four‐membered cycle is reported. Two single nucleophilic CH2 units are delivered to an isothiocyanate as competent electrophilic partner, resulting in the assembly of an imino‐thietane cluster. The double homologation protocol is accomplished directly on a carbon electrophile, not requiring the installation of heteroatom‐centered manifolds.